Star flyers Royal jewel rescue - Learning Company; Riverdeep Interactive Learning Limited ([S.l.] The Learning Co Novato, CA Riverdeep)
Build critical thinking skills in a planet-hopping adventure. Uh-oh! Mom's jewelry is lost. Zoom off with the StarFlyers and see how this dilemma turns into an amazing outer-space mission to rescue the Royal Jewels
"Adventure no. 1"--Container
Ages 5-8
Title from disc label
1
Keywords: CD.ROM (Children ); Critical thinking -- Juvenile software; Educational games -- Juvenile software; Problem solving -- Juvenile software